2017
DOI: 10.5194/nhess-17-2041-2017
|View full text |Cite
|
Sign up to set email alerts
|

Global ship accidents and ocean swell-related sea states

Abstract: Abstract. With the increased frequency of shipping activities, navigation safety has become a major concern, especially when economic losses, human casualties and environmental issues are considered. As a contributing factor, the sea state plays a significant role in shipping safety. However, the types of dangerous sea states that trigger serious shipping accidents are not well understood. To address this issue, we analyzed the sea state characteristics during ship accidents that occurred in poor weather or he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 14 publications
1
15
0
2
Order By: Relevance
“…Marine storms are one of the major preoccupations of sea users and marine security services. They are often responsible for significant damage and loss in several sectors of marine activity such as aquaculture [1] and navigation [2,3]; additionally, these storms are responsible for several changes in the coastlines [4,5] and cause damage to coastal and port infrastructure [6][7][8]. The extent of this damage can have a considerable impact on the economies of countries.…”
Section: Introductionmentioning
confidence: 99%
“…Marine storms are one of the major preoccupations of sea users and marine security services. They are often responsible for significant damage and loss in several sectors of marine activity such as aquaculture [1] and navigation [2,3]; additionally, these storms are responsible for several changes in the coastlines [4,5] and cause damage to coastal and port infrastructure [6][7][8]. The extent of this damage can have a considerable impact on the economies of countries.…”
Section: Introductionmentioning
confidence: 99%
“…Toffoli et al (2005) found that most wave heights are less than 4 m when shipwrecks occur, and shipwrecks are most likely to occur when wind and waves coexist and the crossing wave is at a certain angle or when the sea state grows rapidly. Zhang and Li (2017) reported that although shipwreck incidents are prone to occur during strong wind and wave events, more than half of these incidents have occurred when the wave heights were small. They further found that shipwrecks readily occur when the direction and frequency of swells and sea winds are not significantly different.…”
Section: Analysis In Swell Warning Modulementioning
confidence: 99%
“…A Organização das Nações Unidas para a Alimentação e a Agricultura (FAO) relata que aproximadamente 60 milhões de pessoas atuam na pesca (FAO, 2018). A insegurança da atividade está relacionada tanto às condições meteoceanográficas do ambiente marinho (tempestades, ondas, ventos, chuva, raios) quanto às características da pesca artesanal em si, tais como tamanho da embarcação e equipamentos de navegação rudimentares (Zhang & Li, 2017;Alves et al, 2018;FAO, 2018).…”
Section: Introductionunclassified
“…Entre os anos de 2001 e 2010, foram identificados nos oceanos Atlântico, Pacífico e Índico 755 acidentes com embarcações em alto mar causados por condições meteoro-oceanográficas adversas, tais como ondulações oceânicas (swell) (Zhang & Li, 2017). Apesar desses registros, informações de acidentes envolvendo embarcações de pesca artesanal ainda são incipientes para países com extensa faixa costeira, como o Brasil.…”
Section: Introductionunclassified